Who was Steve Jobs? - Biography - Pollack, Pam.; Belviso, Meg. (New York : Grosset & Dunlap, 2012)
Examines the life and accomplishments of computer industry pioneer Steve Jobs, a founder of Apple Computer, Inc.
Who was Steve Jobs? -- Growing up in the Valley -- The birth of Apple -- Up and down- and out -- What's NeXT? -- To infinity and beyond -- Return to Apple -- Think different -- Insanely great -- Timelines -- Bibliography.
Includes bibliographical references (p. 104-105).
Keywords: Jobs, Steve, -- 1955-2011 -- Juvenile literature; Jobs, Steve, -- 1955-2011.; Apple Computer, Inc. -- Juvenile literature; Apple Computer, Inc; Businessmen -- United States -- Biography -- Juvenile literature; Computer engineers -- United States -- Biography -- Juvenile literature; Inventors -- United States -- Biography -- Juvenile literature; Businessmen -- United States -- Biography; Computer engineers -- United States -- Biography; Inventors -- United States -- Biography